2016
DOI: 10.1111/head.12993
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Alterations in Medication‐Overuse Headache

Abstract: Corroborating previous volumetric results, our study adds information on the putative neurobiological mechanisms involved in MOH, suggesting neurodevelopmental changes in MOH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 55 publications
(108 reference statements)
3
15
1
2
Order By: Relevance
“…Consistent with functional data, results of structural imaging reveal abnormalities within major regions of the mesocortical-limbic circuit in patients with MOH, including less orbitofrontal cortex volume and thickness (23,24,26). Results of several studies suggest that patients with better treatment response to medication withdrawal had more orbitofrontal volume at baseline, i.e., before withdrawal compared to patients who did not respond successfully to medication withdrawal (23,25).…”
Section: Brain Structure and The Orbitofrontal Cortexsupporting
confidence: 55%
See 1 more Smart Citation
“…Consistent with functional data, results of structural imaging reveal abnormalities within major regions of the mesocortical-limbic circuit in patients with MOH, including less orbitofrontal cortex volume and thickness (23,24,26). Results of several studies suggest that patients with better treatment response to medication withdrawal had more orbitofrontal volume at baseline, i.e., before withdrawal compared to patients who did not respond successfully to medication withdrawal (23,25).…”
Section: Brain Structure and The Orbitofrontal Cortexsupporting
confidence: 55%
“…Compared to healthy controls, Riederer et al (26) found higher cortical gyrification over the temporal and occipital cortex in MOH (but not over the orbitofrontal cortex). In addition, patients with higher occipital pole gyrification had poorer response to medication withdrawal.…”
Section: Brain Structure and The Orbitofrontal Cortexmentioning
confidence: 97%
“…Taken together, the results of these studies and our study indicate that the number and the severity of post‐traumatic symptoms are associated with brain integrity in frontal and parietal areas. Furthermore, morphological abnormalities in several of these brain regions have previously been demonstrated in pain conditions including chronic back pain, migraine, fibromyalgia, and medication‐overuse headache . Therefore, further investigation is required to determine if the findings of our study are specific for PPTH or if they are generalizable to other chronic pain conditions and other symptoms that occur following concussion.…”
Section: Discussionmentioning
confidence: 82%
“…Furthermore, morphological abnormalities in several of these brain regions have previously been demonstrated in pain conditions including chronic back pain, migraine, fibromyalgia, and medication-overuse headache. [37][38][39][40] Therefore, further investigation is required to determine if the findings of our study are specific for PPTH or if they are generalizable to other chronic pain conditions and other symptoms that occur following concussion.…”
Section: Discussionmentioning
confidence: 99%
“…Previous voxel-based morphometry (VBM) 12 or surface-based morphometry 15 studies analyzed gray matter volume (GMV) or cortical thickness based on clusters but whether the more macroscopic volume of brain regions altered was unknown. Other volume studies adopted focal region of interest 11 and could not reflect the more widespread volume alteration over the whole brain.…”
Section: Discussionmentioning
confidence: 99%